Pengaruh Kepribadian HEXACO dan Tawakal Terhadap Grit Mahasiswa Fakultas Psikologi UIN Jakarta Menghadapi Mata Kuliah Statistika - Salmanto, Fauzan (TAZKIYA Journal of Psychology, 2020)
This research was conducted to find out the significance of the HEXACO personality and tawakal on grit on 170 students in Faculty of Psychology UIN Syarif Hidayatullah, Jakarta. Sampling conducted using non-probability sampling.  Instruments used in this study there are three scales, namely Academic Grit scale, Brief HEXACO Inventory Scale, and tawakal scale. Test the validity of the measuring instrument using confirmatory factor analysis (CFA) technique. While the data analysis using multiple regression techniques. The results of this study indicate that there is a significant influence of the trait of HEXACO personality and tawakal on grit in students. The amount of influence of all independent variables on grit is 37.4%, while the rest is influenced by other variables outside this research. While the results of the analysis of the proportion of variance of each variable separately, found the largest contribution to grit is conscientiousness, extraversion, trust to God (Allah), not worry, emotionality, and worship. This research will get better results when using a wider population, to obtain more diverse data and can compare with factors that have not been studied.